2019
DOI: 10.3168/jds.2019-16685
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in composition, properties, and heat-induced changes in bovine milk in a seasonal calving system

Abstract: We determined seasonal variations in the composition and characteristics of bovine milk, as well as heat-induced changes in the physicochemical properties of the milk, in a typical seasonal-calving New Zealand herd over 2 full milking seasons. Fat, protein, and lactose contents varied consistently during the year in patterns similar to those of the lactation cycle. Seasonality also had significant effects on milk calcium, ionic calcium, fat globule size, buffering capacity, and ethanol stability, but not on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
105
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 57 publications
13
105
1
1
Order By: Relevance
“…Protein, fat, lactose, and minerals are the four major components in all milks, irrespective of the species ( 18 ); the composition of milk within the same species varies considerably because of various factors, such as breed, stage of lactation, milking interval, type of feed, and climate ( 7 , 19 ). For example, Li et al ( 26 ) reported recently that the stage of lactation is a key factor responsible for differences in the compositional and physicochemical properties of dairy cattle milk in a seasonal calving system in New Zealand.…”
Section: Comparative Compositions Of Cattle and Non-cattle Milksmentioning
confidence: 99%
“…Protein, fat, lactose, and minerals are the four major components in all milks, irrespective of the species ( 18 ); the composition of milk within the same species varies considerably because of various factors, such as breed, stage of lactation, milking interval, type of feed, and climate ( 7 , 19 ). For example, Li et al ( 26 ) reported recently that the stage of lactation is a key factor responsible for differences in the compositional and physicochemical properties of dairy cattle milk in a seasonal calving system in New Zealand.…”
Section: Comparative Compositions Of Cattle and Non-cattle Milksmentioning
confidence: 99%
“…In each season of each year, 4 to 6 batches of yogurt were made and analyzed. Detailed information on the herd and the sampling is given in Li et al (2019).…”
Section: Milk Sampling Initial Processing and Characterizationsmentioning
confidence: 99%
“…Seasonality plays a role in altering the composition and physicochemical properties of bovine milk and subsequently affects the quality of dairy products. The effects of seasonal variation are particularly pronounced in seasonal-calving countries such as New Zealand, where most dairy cows calve at the same period of the year (Auldist et al, 1998;Li et al, 2019). A better understanding of the effects of seasonality on the properties of yogurt would allow better control of the product quality and would assist in the development of new types of fermented dairy products to meet ever-changing consumer preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. The nutritional value of milk and dairy products are related to milk composition (Couvreur et al, 2006;Ortiz-Gonzalez et al, 2007;Li et al, 2019). Variation in milk yield and composition can be due to many factors, e.g., genetic differences, feeding regime, or lactation stage (Dhiman et al, 1999;Elgersma et al, 2004;Poulsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%